Impact of the Covid-19 Pandemic on Stocks Market Performance of Service Industry in Indonesia - Soraya Rizfathanty; Dwi Nastiti Danarsari (Green Publisher Indonesia, 2024)
In March 2020, Corona Virus Disease (COVID-19) was officially declared a pandemic. As a result, the economic and financial sectors, especially business activities that involve interactions between people severe due to the physical distancing policy. Several studies have analyzed the impact of the pandemic on the economic and financial sectors, but none have specifically discussed the impact on the service sector, especially in Indonesia. This study aims to analyze the impact of COVID-19 on abnormal returns and abnormal volume of stocks in the service industry in Indonesia. Using the event study method, three business sectors most affected by COVID-19 in the service industry are investigated. Impact of the company's internal factors on the cumulative abnormal return is also examined using the robust least square regression method. This study finds a negative stock market reaction to the pandemic and social distancing announcement, and positive reaction for announcement of national economic recovery program and reopening economic activity with health protocol. All events had a negative impact on the abnormal volume of the stocks. Finally, either size or liquidity is found to be a significant driver of abnormal returns.